2002
DOI: 10.1128/jb.184.11.2978-2986.2002
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy in Periplasmic Binding Protein-Dependent Transport Systems for Trehalose, Sucrose, and Maltose in Sinorhizobium meliloti

Abstract: We have identified a cluster of six genes involved in trehalose transport and utilization (thu) in Sinorhizobium meliloti. Four of these genes, thuE, -F, -G, and -K, were found to encode components of a binding proteindependent trehalose/maltose/sucrose ABC transporter. Their deduced gene products comprise a trehalose/ maltose-binding protein (ThuE), two integral membrane proteins (ThuF and ThuG), and an ATP-binding protein (ThuK). In addition, a putative regulatory protein (ThuR) was found divergently transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 44 publications
3
72
0
Order By: Relevance
“…A plasmid fusion to SMb20325 was constitutive, but a fusion containing the upstream regulator (SMb20324) and the proposed promoter of SMb20325 was induced 6-fold by trehalose. This result agrees with Jensen et al (19), who found that although the Thu system of S. meliloti transported the ␣-glucosides trehalose and maltose, it was only induced by trehalose. In contrast, the S. meliloti ␣-glucoside transporter, Agl (20), transports sucrose, maltose, and trehalose and was induced by sucrose and to a lesser extent trehalose (19).…”
Section: Site the Results Are Shown In Full Insupporting
confidence: 93%
See 1 more Smart Citation
“…A plasmid fusion to SMb20325 was constitutive, but a fusion containing the upstream regulator (SMb20324) and the proposed promoter of SMb20325 was induced 6-fold by trehalose. This result agrees with Jensen et al (19), who found that although the Thu system of S. meliloti transported the ␣-glucosides trehalose and maltose, it was only induced by trehalose. In contrast, the S. meliloti ␣-glucoside transporter, Agl (20), transports sucrose, maltose, and trehalose and was induced by sucrose and to a lesser extent trehalose (19).…”
Section: Site the Results Are Shown In Full Insupporting
confidence: 93%
“…This result agrees with Jensen et al (19), who found that although the Thu system of S. meliloti transported the ␣-glucosides trehalose and maltose, it was only induced by trehalose. In contrast, the S. meliloti ␣-glucoside transporter, Agl (20), transports sucrose, maltose, and trehalose and was induced by sucrose and to a lesser extent trehalose (19). In our hands, a reporter gene fusion integrated into aglE, (SMc03061) encoding the SBP, was induced by sucrose and maltose but also by the previously undescribed inducers maltotriose (Glc1-4Glc1-4Glc) and turanose (Glc3-4Fruc) ( Table 2), with the caveat that the trisaccharide may either contain, or be converted to, a disaccharide.…”
Section: Site the Results Are Shown In Full Insupporting
confidence: 93%
“…A similar redundancy was found in Sinorhizobium meliloti, where two maltose/trehalose/sucrose ABC transporters were characterized (23,44). One of them (encoded by thuEFGK) is primarily targeted toward trehalose, whereas the second one (encoded by aglEFGAK) is induced primarily by sucrose and to a lesser extent by trehalose (23).…”
Section: Discussionsupporting
confidence: 53%
“…In the genome of the hyperthermophilic bacterium T. maritima, two putative maltose-binding proteins sharing very high sequence similarity (around 80%) were found (31). A similar redundancy was found in Sinorhizobium meliloti, where two maltose/trehalose/sucrose ABC transporters were characterized (23,44). One of them (encoded by thuEFGK) is primarily targeted toward trehalose, whereas the second one (encoded by aglEFGAK) is induced primarily by sucrose and to a lesser extent by trehalose (23).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation